2006
DOI: 10.1002/jor.20249
|View full text |Cite
|
Sign up to set email alerts
|

Development of partial thickness articular cartilage injury in an ovine model

Abstract: The purpose of this study was to create a controlled partial thickness cartilage lesion in a sheep model, and to provide a foundation to study the natural history of the progression of this lesion. Twenty-eight sheep divided into four groups (1, 12, 24, and 52 weeks, n ¼ 7/group) were used in this study. In one stifle, a mechanical tool was used to create a 200 mm partial thickness lesion (1.5 Â 1.5 cm 2 ) on the medial femoral condyle via arthroscopy. Joint fluid was drawn presurgery and after euthanasia for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 44 publications
2
28
0
3
Order By: Relevance
“…However, few studies have focused on alterations in cartilage surrounding a partial-thickness articular cartilage defect. Lu et al [18] reported ongoing degeneration of cartilage surrounding the defect in a sheep model during the course of 52 weeks. Because rabbits often are used as a model to test novel cartilage repair techniques, Hunziker and Quinn [14] reported a considerable number of chondrocytes were lost from cartilage adjacent to surgically created partial-thickness articular cartilage defects, whereas the synthetic activity of the remaining chondrocytes remained unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have focused on alterations in cartilage surrounding a partial-thickness articular cartilage defect. Lu et al [18] reported ongoing degeneration of cartilage surrounding the defect in a sheep model during the course of 52 weeks. Because rabbits often are used as a model to test novel cartilage repair techniques, Hunziker and Quinn [14] reported a considerable number of chondrocytes were lost from cartilage adjacent to surgically created partial-thickness articular cartilage defects, whereas the synthetic activity of the remaining chondrocytes remained unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…This impact force was within or above the range of deleterious impact forces reported for intact joints or osteochondral segments in other animal species such as the rabbit 37,38 and bovine, 24 and the resulting injury was larger than a similar model that used partial thickness defects in this species. 39 Rabbits, or a laboratory animal model, may have been more convenient and allowed larger group sizes for these studies, but the mechanism of action for BMP-7 includes some aspects of improved cartilage repair; therefore, we were reluctant to use a species such as the rabbit that retains intrinsic repair capacity in adulthood. 40 The large body weight, flock behaviors, and housing conditions of these sheep ensured that traumatic injuries would receive regular loading to make partial thickness cartilage injuries progress.…”
mentioning
confidence: 99%
“…No presente experimento o artroscópio foi inserido por acesso craniolateral realizado na altura da eminência do platô tibial e lateral ao ligamento patelar, e portal instrumental medial ao ligamento patelar e na altura do portal craniolateral. Outros experimentos com ovinos também inseriram o artroscópio por acesso lateral e demais instrumentais de apoio pelo acesso medial, sendo que um utilizou o artroscópio para avaliar o efeito da radiofreqüência monopolar em defeitos cartilaginosos da tróclea femoral (Lu et al 2000) e outro para induzir uma lesão na superfície central do côndilo medial (Lu et al 2006).…”
Section: Resultsunclassified
“…Os ovinos apresentam um grande coxim adiposo infrapatelar que preenche a porção dorsal do espaço articular femorotibial, unindo e obscurecendo o ligamento cruzado cranial (Allen et al 1998). Sendo assim, da mesma forma que em cães, faz-se necessária a remoção da gordura infrapatelar, a fim de criar um espaço maior para visibilizar as estruturas (Ryssen et al 2003, Tatarunas & Matera 2004, Lu et al 2006.…”
Section: Resultsunclassified
See 1 more Smart Citation